Gaining Soft Tissue with a Hydrogel Soft Tissue Expander: A Case Report - Uijlenbroek, Henri J.J.; Liu, Yuelian; Wismeijer, Daniel (European Journal of Dentistry, 2022)
In this case report, we describe the treatment of a patient referred to our clinic with a hopeless tooth 21 with an attached pontic. The aim of this case report was to, first, describe the advantages and disadvantages of gaining soft tissue with a self-inflating soft tissue expander before performing a bone augmentation procedure in implant dentistry in the esthetic zone. Second, we describe how an amalgam tattoo, caused by a previously performed apicoectomy that made the extension of the raised flap to cover the augmented site esthetically undesirable, was removed. Two silicone enveloped Osmed hydrogel self-inflating soft tissue expanders were placed submucosally on the right- and left-hand side of the amalgam tattoo. One of these two perforated the overlaying mucosa after 24 days. Both tissue expanders were removed, the amalgam tattoo was excided, the site augmented, and an implant with a crown and a pontic was placed.
Keywords: hydrogel; tissue expander; amalgam tattooing; bone augmentation; implant